Sequential olefination–dimerisation of benzylic dithioacetals by the nickel-catalysed reaction with methyl Grignard or zinc reagent. Issue 16 (28th March 2022) - Yu, Lei; Lai, Guo-Qiao; Zhang, Pinglu; Li, Ze; Luh, Tien-Yau
Abstract : The nickel-catalyzed olefination of benzylic dithioacetal with MeMgI or the corresponding zinc reagent generates Mg(ii ) or Zn(ii ) mercaptide which converts 2-arylpropene into dimer regioselectively. Abstract : Products of main group elements from cross-coupling reactions have been shown to serve as Lewis acids, mediating further reactions of organic coupling products. Thus, the nickel-catalysed olefination of benzylic dithioacetal with MeMgI in benzene in a sealed Schlenk tube at 130 °C generates magnesium mercaptide which regioselectively converts 2-arylpropene into a dimer in good yield. Aryl iodide reacts with 2-propenylmagnesium bromide in the presence of 1, 2-ethanedithiol and NiCl2 (PPh3 )2 to yield the same dimer. Replacement of the Grignard reagent by an organozinc reagent gives the dimers in a better yield.